The emerging role of estrogen's non-nuclear signaling in the cardiovascular disease - Tokiwa, Hiroyuki; Ueda, Kazutaka; Takimoto, Eiki (Frontiers in Cardiovascular Medicine, 2023)
Sexual dimorphism exists in the epidemiology of cardiovascular disease (CVD), which indicates the involvement of sexual hormones in the pathophysiology of CVD. In particular, ample evidence has demonstrated estrogen's protective effect on the cardiovascular system. While estrogen receptors, bound to estrogen, act as a transcription factor which regulates gene expressions by binding to the specific DNA sequence, a subpopulation of estrogen receptors localized at the plasma membrane induces activation of intracellular signaling, called “non-nuclear signaling” or “membrane-initiated steroid signaling of estrogen”. Although the precise molecular mechanism of non-nuclear signaling as well as its physiological impact was unclear for a long time, recent development of genetically modified animal models and pathway-selective estrogen receptor stimulant bring new insights into this pathway. We review the published experimental studies on non-nuclear signaling of estrogen, and summarize its role in cardiovascular system, especially focusing on: (1) the molecular mechanism of non-nuclear signaling; (2) the design of genetically modified animals and pathway-selective stimulant of estrogen receptor.